Coronary slow-flow phenomenon in takotsubo syndrome: the prevalence, clinical determinants and long-term prognostic impact. (14th October 2021) - Stepien, K; Nowak, K; Stepien, A; Nessler, J; Zalewski, J
Abstract: Background: Previous studies demonstrated that patients with takotsubo syndrome (TTS) may present with coronary slow-flow (CSF) at coronary angiography performed in the acute phase [1]. However, the exact clinical relevance and its long-term prognostic impact have not been established yet. In the only recently published study Montone et al. proved that TTS patients with CSF were characterized by a worse clinical presentation with higher rate of intrahospital complications and poor long-term clinical outcome [2]. Purpose: We sought to investigate the prevalence of CSF in TTS patients, its determinants and long-term prognostic impact. Methods: Among 7771 myocardial infarction patients hospitalized in our center in 2012–2019 years, we identified 82 (1.1%) TTS patients with performed coronary angiography (Figure 1A). The coronary flow was assessed quantitatively with TIMI Frame Count (TFC), whereas myocardial perfusion with TIMI myocardial perfusion grade (TMPG). The clinical and angiographic characterstics of 67 TTS patients complying with MINOCA definition were compared with representative 50 non-TTS MINOCA (Figure 1A). Results: CSF (TIMI 2) was identified in 33 (40.2%) TTS patients. CSF-TTS patients were characterized with higher TFC and worse TMPG in each analyzed coronary vessel (Figure 1B). CSF was observed in LAD artery in each patient, in 78.8% in LCx and in 33.3% in RCA, respectively. In CSF-TTS lower values of LVEF on admission (33.5 (25–40) vs 40 (35–45)%, P=0.019) as well as more frequent midventricular TTS (27.3 vs 8.2%, P=0.020), nearly normal coronary arteries (<30% stenosis) (75.8 vs 49.0%, P=0.015) and coexistence of both physical and emotional triggers (9.1 vs 0%, P=0.032) were noted. Moreover, CSF was observed significantly more frequent than in non-TTS MINOCA (44.8 vs 10.0%, P<0.001) with different distribution in particular vessels (P<0.001). In median 55 months of long-term observation higher all-cause mortality was stated in CSF-TTS (30.3 vs 10.2%, P=0.024) (Figure 1C) without difference between TTS and non-TTS MINOCA (P=0.42) (Figure 1D). By Cox proportional hazards model the CSF was identified as an independent predictor of long-term mortality (P<0.001). Conclusions: As has been shown high proportion of TTS patients were characterized with remarkably marked myocardial perfusion abnormalities, especially in the left coronary vessels, which were associated with unfavorable long-term prognosis. Our study is the first presenting the direct angiographic, clinical and prognostic comparison of TTS MINOCA and non-TTS MINOCA patients. FUNDunding Acknowledgement: Type of funding sources: None.